Die Bybel: Teks en ondermyning - Philip J. Nel (Hervormde teologiese studies, 2003)
The Bible: Text and subversion This article explores both the subversive dimension of the biblical text, in particular the Old Testament, as the ramifications thereof for the concept of a religious text. It argues that interpretation has been historically and fundamentally part and parcel of the genesis and reception history of the biblical text. The texts of Job and Jonah have been chosen for their explicit subversive strategies. The article shows that if the biblical text exploits strategies of subversion, it also contravenes the traditional opinion subscribing to a referential meaning of texts. A subversive text cannot simultaneously deny and confirm a constant (fixed) and an immutable reality. The article argues that biblical scholars should reconsider other perceptions of the religious text to avoid the destructive criticism of referential meaning in postmodern studies. One option to be considered is the view of a text as performative communication.